Non-alcoholic fatty liver disease (NAFLD): a significant predictor of gestational diabetes mellitus (GDM) and early pregnancy miscarriages—prospective study in Rajarata Pregnancy Cohort (RaPCo) - Suneth Buddhika Agampodi; Iresha Sandamali Koralegedara; Janith Niwanthaka Warnasekara; Korale Gedara Dayaratne; Farika Nirmani De Silva; Jagath Keerthi Premadasa (BMJ Open Gastroenterology)
Background and aims Non-alcoholic fatty liver disease (NAFLD) is increasing globally with a mounting body of evidence on various adverse effects on pregnancy. Yet, prospective studies, especially from low-income and middle-income countries, are lacking in examining the impact of NAFLD in pregnancy. In this study, we explored the effect of NAFLD on the development of gestational diabetes mellitus (GDM) and early pregnancy miscarriages.Methods A population-based prospective cohort study was conducted among first-trimester pregnant women who registered in the national pregnancy care programme during July–September 2019 in Anuradhapura district, Sri Lanka. Baseline clinical–biochemical parameters and ultrasound scan (USS) of the liver were done to assess fatty liver. Those who were normoglycaemic based on WHO criteria were followed up, and a repeat oral glucose tolerance test was performed between 24 and 28 weeks of gestation.Results Of the 632 pregnant women studied, 90 (14%) and 234 (37%) were diagnosed as having fatty liver grade (FLG) II and I, respectively. The cumulative incidence of GDM in FLG 0, I, and II were 11, 44, and 162 per 1000 pregnancies, respectively. After adjusting for age and other known risk factors, women with FLG II had a relative risk (RR) of 12.5 (95% CI 2.2 to 66.4) for developing GDM compared with FLG 0. In addition, women with FLG I (RR 2.1, 95% CI 1.01 to 4.64) and FLG II (RR 4.5, 95% CI 2.1 to 9.9) were significant risk factors for early pregnancy miscarriages, and FLG II remained as the only independent predictor of miscarriages after adjusting for age, parity, body mass index, blood sugar, blood pressure, and haemoglobin level (adjusted OR 4.2 (95% CI 1.9 to 9.1)).Conclusion In this rural south Asian community, NAFLD is shown to be a major risk factor for GDM and early pregnancy miscarriages. Therefore, routine identification of NAFLD through a simple USS may help in the early identification of high-risk mothers.